EFFCT OF SEASON ON TESTICULAR AND EPIDIDYMAL MEASUREMENTS OF LOCAL BLACK BUCKS - Ahmed, Ali Sh.; Hobi, Abd AL-Kareem A.; G. , Hadair A. (Diyala Agricultural Sciences Journal, 2016)
The Testes samples were harvested from local slaughtered of local black goats in Almqudadia carnage . black local Bucks about 1-3 years estimated by data examination . The samples were 10 testes of each month, starting from 15 July 2012 to 15 July 2013. The samples were excised from bodies of slaughtered animals. The extracted samples were cleared from adjacent structures. The samples were immersed in isotonic saline solution with ice packs during transportation to the experimental lab. Morphometric,The results showed increased significantly during autumn to weight , volume , length and width to reached 155.94±1.21 gm, 138.133±1.32 cm3 , 10.62±10.62, cm 27.7±0.11and 26.14±1.21cm respectively, compare with other seasons .Total weight of epididymis increased significantly during the autumn to reach (17.52±3.27gm) compare with (13.26±4.18 gm), (11.51±1.11 gm) and (11.60±2.13 gm) during the winter ، the spring and the summer respectively investigated showed the cauda of epididymis reached highest weight during the autumn (7.71±0.20 gm) and lowest weight during the winter ، the summer (4.48±0.30 gm (. conclusion the autumn season effect significantly in testicular changes and reproductive season beginning in black local Bucks.